Pemodelan Matematika dan Simulasi Kecanduan Berbelanja Online pada Aplikasi Shopee Tipe SEIR - Naitili, Adriana; Obe, Leonardus Frengky; Bano, Elinora Naikteas (Saintek Lahan Kering, 2023)
Shopee is an online shopping application that is easy to use with customers' smartphones anytime and anywhere. The presence of Shopee can make it easier for users to shop for goods/services products via smartphones without the need to use a computer. Shopee sells all kinds of needs such as household needs, fashion, watches, cellphones, accessories, beauty, and so on. Without realizing it, Shopee has a negative impact on users who use it continuously so that it becomes a habit / addiction. Online shopping results in waste because shopping is not according to need but desire because it does not have high self-control, resulting in stress or depression. This study aims to build a mathematical model of online shopping addiction in the SEIR type Shopee application. Based on the research results, two equilibrium points are obtained, namely the equilibrium point free of online shopping addiction on the Shopee application and will be stable when and the equilibrium point there is online shopping addiction on the Shopee application and will be stable when . Simulation results are observed in two conditions, namely when , the value of is obtained, meaning that the rate of people interacting with people who are addicted to online shopping at Shopee is still small, causing the rate of groups of people who create accounts to shop and eventually become addicted to online shopping. When , the value of is obtained, meaning that the rate of people interacting with people who are addicted to online shopping in the Shopee application has increased, causing the rate of groups of people who create accounts in the Shopee application and eventually become addicted to shopping online at Shopee to increase over time.